Rekonstruksi Tata Kelola Pendidikan Islam Berbasis Teologi - Rizal Anshorudin; Ilham Nurjaman; Eva Saufana; Adang Hambali; Hasan Basri (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2026)
Islamic educational institutions currently face demands for public accountability and digital transformation, while the imperative to preserve the theological values underlying their existence must still be met. Studies on Islamic-based governance remain largely theoretical, normative, and fragmented, lacking a synthesis of how theological foundations are translated into operational educational-governance constructs. This study develops an integrative conceptual model through two analytical steps: systematically mapping the theological foundations underlying Islamic education in reputable literature, and analyzing how these foundations are transformed into governance constructs and practices. The study adopts a qualitative approach using the Systematic Literature Review (SLR) method following the PRISMA 2020 protocol. 28 articles published between 2021 and 2026 were synthesized using thematic synthesis combined with qualitative content analysis. The synthesis shows that theological values such as tawhīd, amānah, shūrā, and 'adl function as generative constructs increasingly operationalized through visionary leadership, quality culture, and digital/AI-based governance. This study proposes the Tauhid-Based Educational Governance Framework (TBEGF), an integrative model explaining four interrelated stages of transformation: theological foundation, internalization, organizational governance, and governance outcomes. Theoretically, TBEGF positions theology as a generative source of governance mechanisms, extending Islamic leadership scholarship from theology toward governance. In practice, the framework serves as an operational reference for madrasah, pesantren, and Islamic higher-education leaders to align institutional accountability with theological authenticity, while laying the groundwork for further empirical validation through Structural Equation Modeling.